2017
DOI: 10.15761/ccrr.1000355
|View full text |Cite
|
Sign up to set email alerts
|

Retinal epithelitis as ocular side effects of oral biphosphonates

Abstract: Alendronate is a new bisphosphonate, primarily used for the treatment of osteoporosis and several other bone diseases. Herein we report a case of a patient showing an acute retinal pigment epithelitis (ARPE) following oral administration of alendronate due to osteoprosis. A 50-year old female referred to our observation complaining visual blurring and metamorphopsia in her left eye. She did not report ocular impairment in the past. Her clinical history was unremarkable for any systemic disease except she had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(4 reference statements)
1
1
0
Order By: Relevance
“…Previous studies have reported a good visual acuity recovery in most of the ARPE cases within 6-12 weeks. 6,10,11 Recovery was also seen in our patient, and visual acuity of 10/10 returned within 25 days. The vision quality still had not improved to the level of the fellow eye by final follow-up at 19 months (persistent micropsia and metamorphopsia).…”
Section: Diagnosis and Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous studies have reported a good visual acuity recovery in most of the ARPE cases within 6-12 weeks. 6,10,11 Recovery was also seen in our patient, and visual acuity of 10/10 returned within 25 days. The vision quality still had not improved to the level of the fellow eye by final follow-up at 19 months (persistent micropsia and metamorphopsia).…”
Section: Diagnosis and Discussionsupporting
confidence: 75%
“…ARPE is a self-limiting inflammatory disease. 6,[9][10][11][12][13] Given its rarity, only a few cases have been reported in the literature, 6,[9][10][11]13 and its pathophysiology and etiology are not well understood. 10 Several studies suggest that the junction between cone outer segments and RPE cells is the initial site of inflammation.…”
Section: Diagnosis and Discussionmentioning
confidence: 99%